A new species of Metaphycus Mercet (Hymenoptera: Encyrtidae) from Mexico and key to the species of the genera parasitizing whiteflies (Hemiptera: Aleyrodidae) in the Neotropical region. - Myartseva, Svetlana N.; Ruíz Cancino, Enrique (Instituto de Ecología, A.C., 2010)
Metaphycus cerealis sp. nov., a parasitoid of the whitefly Aleurocybotus occiduus (Russell) from the State of Sinaloa, Mexico, is described. A key to species of Metaphycus parasitizing whiteflies in the Neotropic Region is given.